An analysis of some school history textbooks with special reference to styles of concept presentation - Matoti, Sukude Mangwevandile (Rhodes University, Faculty of Education, Department of Education, 1990)
The aim of this study was to find out whether the school history textbooks used in Transkei Junior and Senior secondary schools were adequate in helping pupils meet the demands of their course. The results of the study would be used as argument for or against the assumption that the type of textbooks used in Transkei schools, through their inadequacy in equipping the pupils with the necessary skills for "doing" history, do contribute to the high failure rate in history, especially that they are in most schools, the only recourse for both the teacher and the pupil. In particular the study intended to see what strategies the history textbooks used to aid concept understanding which is crucial to the understanding of history. Twenty three criteria, fourteen objective and nine subjective were used to assess the books for readability and for strategies which might aid concept understanding. Eight books were assessed: four Std 5 and four Std 8 books. The results showed that only three of the eight books catered for the development of skills of learning history and were suited to the level of the pupiils for whom they were intended . History textbooks therefore need to be improved so as to foster the skills of learning history. Their inadequacy could be a contributory factor to the high rate of failure. In-service and pre-service training in methods of textbook analysis can assist in textbook selection and for changes in methods of teaching to supplement shortcomings in books which are commonly used
Keywords: History -- Study and teaching -- South Africa -- Textbooks -- Evaluation; South Africa -- History -- Textbooks